Mansour Fakih's Gender Analysis of the Fulfillment of Husband And Wife's Rights and Obligations In Sirri Marriage: Case Study in Padangsidimpuan City, West Sumatra Province, Indonesia - Doli Bastian Ali Saputra Nasution; Zainul Fuad; Sukiati Sukiati (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
This study analyzes the practice of sirri marriage in the City of Padangsidimpuan, Province of West Sumatra, Indonesia. The focus of this research is to see whether gender bias occurs according to gender analysis according to Mansour Fakih in fulfilling the rights and obligations of husband and wife in unregistered marriage families in Padangsidimpuan City. This type of research is field qualitative with the approach of Legal Sociology, Legal Psychology, and Anthropology. Based on research findings, unregistered marriages in the city of Padang Sidempuan do not only have an impact on wives and children, but also have an impact on husbands both in the household and in social life including 1) Marginalization, such as husbands having difficulty getting their rights from where they work and it is difficult to get social assistance from the government because they do not have a marriage certificate and family card, 2) Subordination: the impression that women are objects in marriage so that a woman can be published as a wife or kept secret, 3) Stereotypes: Women who are married in unregistered ways are considered mistresses , having an affair, or living at home without being married, 4) Violence: unregistered marriages are prone to domestic violence because there is no evidence that shows the existence of marital ties, and 5) double burden that must be borne by the wife, namely having to earn a living that should be borne by the husband, as well as take care and care for their children